Kinerja Retribusi Parkir dalam Mendukung Pendapatan Asli Daerah: Analisis Pertumbuhan, Efektivitas, dan Kontribusi di Kota Kupang - Albina Des; Marius Masri; Maria Imakulata Pongge (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the growth, effectiveness, and contribution of parking levies to the Regional Original Revenue (PAD) of Kupang City during the 2015–2023 period. The study is motivated by the importance of optimizing PAD to support regional fiscal independence, while parking levies, as one of the sources of PAD, have not yet made an optimal contribution. This research employed a descriptive quantitative approach supported by qualitative data. The main data, consisting of parking levy targets and realizations as well as PAD realizations, were obtained from the Kupang City Transportation Office and the Regional Financial and Asset Management Agency of Kupang City, while supporting data were collected through semi-structured interviews. The results show that parking levy revenue increased nominally from Rp889,115,100 in 2015 to Rp3,194,281,900 in 2023; however, its growth was fluctuating and experienced a decline in 2019. The effectiveness of levy collection during the 2015–2018 period was categorized as effective to highly effective, whereas during the 2019–2023 period it declined and was categorized as less effective. The contribution of parking levies to PAD during the study period ranged only from 0.63% to 1.68%, indicating a very low contribution. This study concludes that parking levies have the potential to be improved, but this requires better governance, stronger supervision, and the digitalization of the collection system in order to enhance their contribution to the PAD of Kupang City.